Preparing to Evacuate your Home in Case of an Emergency - Elizabeth B. Bolton (EDIS)
During these times of potential terrorist attacks, it is important to plan for the worst and hope that it never happens. For example, you and your family may be asked to leave your home due to some emergency situation in your community. Your local emergency officials will not ask you to leave your home or location unless there is a valid reason. Most of the time these requests and related information will come through radio broadcasts or the local TV station. Different warning methods may be used such as a siren or telephone calls. Stay tuned and follow the directions and the evacuation routes recommended by the emergency officials. The most important thing to keep in mind is to have a plan for a possible evacuation. Be prepared to evacuate and keep the suggestions in this paper in mind.